A Weekend in the Country "Rural Retreat", a think tank for artistic directors - McCarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2003)
A think tank for artistic directors. PALABRAS CLAVE: Assis Carreiro, Rural Retreats, international think tanks, artistic directors.